الآليات القانونية لعقود المناولة في ظل قانون الصفقات العمومية - يوسف, دباخ (جامعة الوادي.University eloued, 2021)
"وبعـد القيام بالدراسـة والتحليل لموضوع المناولة في مجال الصفقات العمومية تـم التوصـل إلـى أن المناولــة تعد أسلوب لتوفير مكونات الإنتاج الصناعي و المساهمة في زيادة النسيج الإقتصادي، كما انها تعتبر وسيلة لزيادة النجاعة الإقتصادية و النهوض بالأقتصاد الوطني و ذلك لكونها تتميز بالتخصيص و المرونة و الإبداع و تنفذ الجزء الممنوح لها في الصفقة العمومية بسرعة، و هذا ما جعل المشرع يعطيها اهتمام اكثر في السنوات األخيرة و ذلك بإصدارة العديد من القوانين و التنظيمات المنظمة للصفقات العمومية و ترقيتها من أجل تدارك النقص الذي كان حاصل فيها. لنخلص في النهاية إلـى ضـرورة قيـام الشـركات الكبيرة الجزائرية بـدور فعـال فـي تنمية المناولـة الوطنية والحـد مـن الإعتمـاد علــى المناولــة الخارجية خدمـة لمصـالحها وقــدراتها التنافسية والمساهمة في التنمية الاقتصادية، وذلك بتفعيل دور المؤسسات الصغيرة والمتوسطة كونها تعتبر مصدرا الافكار الإبداعية حيث يسمح لها هذا الإبداع والتمييز في كسب الزبائن وزيادة تنافسيتها. مما يحتم على المؤسسات الصناعية في الدول النامية، ضرورة تبني هذه الإستراتيجية من أجل تنمية وترقية منتجاتها والرفع من ميزتها التنافسية محليا ودوليا."" After conducting the study and analysis of the subject of handling in the field of public transactions, it was found that handling is a method to provide the components of industrial production and contribute to the increase of the economic fabric. It is also a means to increase economic efficiency and promote the national economy because it is characterized by privatization, flexibility and creativity. The part granted to it in the public deal quickly, and this has made the legislator give it more attention in recent years and the issuance of many laws and regulations governing public transactions and promotion in order to remedy the shortfall that it was. Finally, we conclude that large Algerian companies should play an active role in developing national handling and reducing reliance on external handling to serve their interests and competitiveness and contribute to economic development by activating the role of small and medium enterprises as a source of creative ideas. And increase their competitiveness. Which necessitates the industrial institutions in developing countries, the need to adopt this strategy for the development and promotion of its products and to increase its competitive advantage locally and internationally. "
قانون اداري
Keywords: المناولة، الصفقات العمومية، التشريع الجزائري.; Handling, public transactions, Algerian legislation